Rapid, collaborative generation and review of COVID-19 pandemic-specific competencies for family medicine residency training - Wooltorton, Eric; Seale, Edward; Lewis, Denice; Noel, Kendall; Liddy, Clare; Viner, Gary; Shoppoff, Lina; Archibald, Douglas (Canadian Medical Education Journal, 2020)
Background: In March 2020, the COVID-19 pandemic disrupted competency-based medical education in Family Medicine programs across Canada. Faculty and residents identified a need for clear, relevant, and specific competencies to frame teaching, learning, supervision and feedback during the pandemic. Methods: A rapid, iterative, educational quality improvement process was launched. Phase 1 involved experienced educators defining gaps in our program’s existing competency-database, reviewing emerging public health and regulatory guidelines, and drafting competencies. Phase 2 involved translation, member-checking, and anonymous feedback and editing of draft competencies by residents and other educational leaders. Phase 3 involved wider dissemination, collaborative editing and feedback from residents and faculty throughout the department. Results: A total of 44 physicians including residents and faculty from multiple contexts provided detailed feedback, review, and editing of an ultimate list of 33 competencies organized by CanMEDS-FM roles. Broad agreement was obtained that the competencies form reasonable learning outcomes during the COVID-19 pandemic. Conclusions: These competencies represent learning objectives reflecting the initial educational mindsets of a wide range of teachers and learners experiencing a global pandemic. The project illustrates a novel collaboration across educational portfolios as a rapid educational response to a public health crisis.